A quantitative structural study of late pan-african compressional deformation in the central eastern desert (Egypt) during Gondwana assembly - Abdeen, Mamdouh Mahmoud; Greiling, Reinhard O. (Gondwana research, 2005)
The Arabian-Nubian-Shield (ANS) is composed of a number of island arcs together with fragments of oceanic lithospere and minor continental terranes. The terranes collided with each other until c. 600 Ma ago. Subsequently, they were accreted onto West Gondwana, west of the present River Nile. Apart from widespread ophiolite nappe emplacement, collisional deformation and related lithospheric thickening appear to be relatively weak. Early post-collisional structures comprise not only extensional features such as fault-bounded (molasse) basins and metamorphic core complexes, but also major wrench fault systems, and thrusts and folds. The Hammamat Group was deposited in fault-bounded basins, which formed due to N-S to NW-SE directed extension. Hammamat Group sediments were intruded by late orogenic granites, dated as c. 595 Ma old. A NNW-SSE-oriented compression prevailed after the deposition of the Hammamat Sediments. This is documented by the presence of NW-verging folds and SE-dipping thrusts that were refolded and thrusted in the same direction. Restoration of a NNW-SSE- oriented balanced section across Wadi Queih indicates more than 25% of shortening. Transpressional wrenching related to the Najd Fault System followed this stage. The wrenching produced NW-SE sinistral faults associated with positive flower structures that comprise NE-verging folds and SW-dipping thrusts. Section restoration across these late structures indicates 15 17% shortening in the NE-SW direction. At a regional scale, the two post-Hammamat compressional phases produced an interference pattern with domes and basins. It can be shown that the Najd Fault System splays into a horsetail structure in the Wadi Queih area and loses displacement towards N and NW. The present study shows a distinct space and time relationship between deposition of Hammamat Group/late-Pan-African clastic sediments and late stages of Najd Fault wrench faulting: Hammamat deposition is followed by two episodes of compression, with the second episode being related to Najd Fault transpression. Therefore, the Hammamat sediments do not represent the latest tectonic feature of the Pan-African orogeny in the ANS. The latest orogenic episodes were the two successive phases of compression and transpression, respectively. It is speculated that extension during (Hammamat) basin formation was sufficiently effective to reduce the thickness of the orogenic lithosphere until it became gravitationally stable, and incapable of further gravitational deformation.